Abnormal Distribution and Function of Monocyte Subsets in Patients With Primary Immune Thrombocytopenia. (October 2017) - Yang, Yanhui; Zhang, Xian; Zhang, Donglei; Li, Huiyuan; Ma, Li; Xuan, Min; Wang, Hongmei; Yang, Renchi
Human monocytes are heterogeneous and play an important role in autoimmune diseases. However, the distribution and function of monocyte subsets remain unclear in primary immune thrombocytopenia (ITP). In this study, we determined the frequencies of monocyte subsets in 71 untreated patients with active ITP and 49 healthy controls by flow cytometry. Compared with controls, the frequency of nonclassical monocytes was significantly increased in patients with active ITP but decreased after complete remission. The intermediate subset was also increased in patients with active ITP and produced the highest levels of tumor necrosis factor α and interleukin 1β. Both the nonclassical and intermediate subsets were negatively correlated with the platelet counts. We further determined the correlation between monocyte subsets and the proliferation of platelet-autoreactive T cells. The purified monocyte subsets were cocultured with CD4 + T cells and autologous platelets. The nonclassical subset showed the highest capability of promoting platelet reactive T-cell proliferation and significantly promoted the secretion of interferon γ among the 3 subsets. In conclusion, the nonclassical and intermediate monocyte subsets are both expanded and play different roles in the pathogenesis of ITP.